A Tandem of Rare Complications Due to Stent Infection - Inga, Botchorishvili; Vakhtang, Kipiani; Rusudan, Agladze; Tamar, Gaprindashvili; Sergo, Khajalia; Zurab, Pagava; Levan, Vashakidze; Vasil, Natsvlishvili (Journal of Clinical Case Reports and Images, 2023)
This report details sequential rare complications arising from a vascular stent infection. Clinical course, microbiology, and imaging are outlined, with emphasis on early recognition and multidisciplinary management. Lessons for device surveillance and antimicrobial stewardship are highlighted.
Keywords: nosocomial infections; coronary wall injury; mortality